2004
DOI: 10.1038/sj.ejhg.5201229
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for height: results of a full genome scan in Dutch sibling pairs

Abstract: Height is a highly heritable, complex trait. At present, the genes responsible for the variation in height have not yet been identified. This paper summarizes the results of previous linkage studies and presents results of an additional linkage analysis. Using data from the Netherlands Twin Register, a sib-pair-based linkage analysis for adult height was conducted. For 513 sib-pairs from 174 families complete genome scans and adult height were available. The strongest evidence for linkage was found for a regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
3
26
2
Order By: Relevance
“…This is consistent with the findings of this as well as other linkage studies on height (e.g., Hirschhorn et al 2001;Xu et al 2002;Wiltshire et al 2002). Typically as shown in all of the genome-wide linkage scans for height so far, among all the regions reported, only very few reached the significance threshold for linkage (LOD>3.0) (for review see Willemsen et al 2004), implicating the difficulty to detect height genes of ''major effects''. Although our study had achieved the largest sample size and most (Sammalisto et al 2005) likely, the highest statistical power in all the genomewide linkage scans for height, we only detected three regions, 9q22, Xq24, and Xp22, of statistically significant linkage to height.…”
Section: Xp22 Xq24supporting
confidence: 90%
“…This is consistent with the findings of this as well as other linkage studies on height (e.g., Hirschhorn et al 2001;Xu et al 2002;Wiltshire et al 2002). Typically as shown in all of the genome-wide linkage scans for height so far, among all the regions reported, only very few reached the significance threshold for linkage (LOD>3.0) (for review see Willemsen et al 2004), implicating the difficulty to detect height genes of ''major effects''. Although our study had achieved the largest sample size and most (Sammalisto et al 2005) likely, the highest statistical power in all the genomewide linkage scans for height, we only detected three regions, 9q22, Xq24, and Xp22, of statistically significant linkage to height.…”
Section: Xp22 Xq24supporting
confidence: 90%
“…Human adult height has been suggested to be highly heritable, with heritability estimates (h 2 ) ranging from 0.5 to 0.9 (Mukhopadhyay and Weeks 2003;Willemsen et al 2004) in various populations and with an h 2 of 0.7 in the Samoan islands (unpublished data). Our simulation study shows that, if the heritability that is explained by a single trait locus ranges from 0.7 to 0.175, the power to detect a linkage signal (genome-wide α = 0.05) to adult height in the current study sample ranges from 31% to 14%.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%
“…These fairly low power estimates suggest that additional chromosome regions not detected in the current study might be of great importance for variation in adult height in the studied population. Since the first genome-wide linkage scans for height were performed in 2001 (Hirschhorn et al 2001;Perola et al 2001), several susceptibility loci for height have been reported [for a recent overview see Perola et al (2007)], but, as for most complex phenotypes, only some have been successfully replicated by further studies (Liu et al 2004(Liu et al , 2006Willemsen et al 2004;Sale et al 2005;Shmulewitz et al 2006). The most promising susceptibility loci for height (Score.Max p = 0.005) detected in our current study of sib-pairs from American Samoa was located on chromosome 9q31 at marker D9S1690.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%
“…However, the list of genes and allelic variants involved in the determination of BS and BG variation is far from being complete. Several genome-wide scans have been conducted to identify susceptibility loci for bone size (e.g., Koller et al 2001;Deng et al 2003b) and adult height variation (e.g., Mukhopadhyay et al 2003;Willemsen et al 2004). With a few exceptions the results of the linkage analyses are so far largely inconsistent.…”
Section: Introductionmentioning
confidence: 99%